Modified Non-Linear Control for microgrid photovoltaic power system / Sharon Serenade Gerang, Muhammad Amirul Osman and Naeem M.S. Hannoon - Gerang, Sharon Serenade; Osman, Muhammad Amirul; Hannoon, Naeem M.S. (Universiti Teknologi MARA Press (Penerbit UiTM), 2020)
This paper presents a Modified Non-Linear Control (MNLC) for microgrid to optimize the performances of microgrid photovoltaic systems during outages/disturbance in distributed generation. This system underlines the adequacy of this proposed control methodology in terms of power management and stability of the system under various scenarios which are solar irradiance, man-made fault, etc.All these scenarios are presented during high loading conditions. This proposed non-linear control is tested at both point of common coupling (PCC) and the receiving end during sudden change of load. The simulated results are compared with PI controller using a software platform, MATLAB, Simulink. The system consists of a photovoltaic (PV) arrays, a DC-DC boost converter, a maximum power point tracker (MPPT) controller, wind turbine, battery and a resistive-inductive load. To validate the performance of the proposed MNLC over conventional designs the PV based Microgrid is subjected to grid side contingency (i.e. dynamic Load variation), as well as distributed generation (dg) side uncertainty (i.e. Partial shading). The performance of proposed MNLC is evidenced effective in MATLAB Simulink environment.